Antibiotic susceptibility and molecular epidemiology of nasopharyngeal pneumococci from Spanish children. - Sánchez-Tatay, D; Arroyo, L; Tarragó, D; Lirola, M; Porras, A; Fenoll, A; Hausdorff, W; Brueggemann, A; Obando, I (2008)
Nasopharyngeal pneumococci were collected from 635 Spanish children aged 6 months to 6 years attending four primary healthcare centres (n = 276) or two hospital emergency rooms (n = 359); 36% of the children had received >/=1 dose of pneumococcal conjugate vaccine (PCV7). Overall, the carriage rate of Streptococcus pneumoniae was 31%, with no significant differences in carriage rates according to setting. Colonization with vaccine serotypes was significantly associated with the absence of PCV7 immunization (29.4% vs. 5.9%, p <0.001). Forty-seven per cent of all isolates were penicillin- and/or erythromycin-non-susceptible; 13 international antibiotic-resistant clones were represented among non-susceptible pneumococci and were similarly distributed among vaccine and non-vaccine serotypes.